2021
DOI: 10.1002/zaac.202100252
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterizations and kinetics of MOF‐5 as herbicide vehicle and its controlled release in PVA/ST biodegradable composite membranes

Abstract: Polyvinyl alcohol/starch based composite membranes containing herbicide‐loaded metal‐organic‐framework (MOF‐5) was successfully synthesized by electrostatic spraying technique. Several main parameters affecting the adsorption of MOF‐5 were studied, including the initial concentration of the herbicide solution, adsorption time, and temperature. Under optimal conditions, herbicide‐loaded MOF‐5 was successfully synthesized and the main properties were characterized by Scanning Electron Microscopy (SEM), X‐Ray Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In a study reported by Lee et al, 88 MOF-5, a zinc terephthalate MOF, was loaded with the herbicide atrazine by dispersing 0.2 g of MOF-5 in 30 mL of 0.030 g/L of atrazine/methanol solution for 3 h. The loaded MOF-5 was then incorporated into a poly(vinyl alcohol)/starch (PVA/ST) composite through electrospinning. Herbicide release studies have shown that incorporating the herbicide inside the MOFs and then into composites provided release rates lower than those from mixing atrazine into the polymer matrix.…”
Section: Mofs For Pesticide Deliverymentioning
confidence: 99%
“…In a study reported by Lee et al, 88 MOF-5, a zinc terephthalate MOF, was loaded with the herbicide atrazine by dispersing 0.2 g of MOF-5 in 30 mL of 0.030 g/L of atrazine/methanol solution for 3 h. The loaded MOF-5 was then incorporated into a poly(vinyl alcohol)/starch (PVA/ST) composite through electrospinning. Herbicide release studies have shown that incorporating the herbicide inside the MOFs and then into composites provided release rates lower than those from mixing atrazine into the polymer matrix.…”
Section: Mofs For Pesticide Deliverymentioning
confidence: 99%
“…77 In parallel, eco-friendly and biodegradable MOF-containing composite membranes designed for slow delivery of herbicides upon membrane decomposition have also been prepared and investigated. 78 Other 82,83 The preparation of MOF-containing composites generally proceeds in two steps but the order of the steps, synthesis of the MOF vs synthesis of the composite, may vary depending on the target hybrid. 84 For instance, the incorporation of metallic nanoparticles inside the pores of MOFs, often designed for catalysis investigations, must proceed via a post-functionalization step, such as the reduction of inorganic guests and pyrolysis of coordination or organometallic complexes in the pores.…”
Section: Composites Of Metal-porphyrinic Frameworkmentioning
confidence: 99%
“…77 In parallel, eco-friendly and biodegradable MOF-containing composite membranes designed for slow delivery of herbicides upon membrane decomposition have also been prepared and investigated. 78 Other examples include composites of cellulose (CelloMOFs), 79 cotton 80 and corncob 81 used for the adsorption and extraction of pesticides. These composites have the advantage of addressing organic molecules regardless of the nature of the samples (in water, complex solids, and soil).…”
Section: Synthesis Of Metal-porphyrinic Frameworkmentioning
confidence: 99%
“…MOFs are well-known for their ultrahigh porosity and surface area. Because of their ability to host different kinds of molecules and allow their controlled release, MOFs have been studied extensively for drug delivery applications. Recently, MOFs have been shown to be useful for the separation and sensing of toxic agrochemicals. Similar to their use in controlled drug delivery, MOFs can potentially act as vector for sustainable delivery of pesticides. However, their crystalline powdered or granular form is a barrier to practical applications. Integration of MOFs in polymer composites can potentially solve this problem with the additional benefit of targeted delivery of pesticides when the composite is in direct contact with the plants, with release being assisted by natural rain or water sprinkler/irrigation systems as illustrated in Scheme .…”
Section: Introductionmentioning
confidence: 99%